Designing a Model Using a Dynamic Systems Approach in the Utilization of Nickel Slag Waste - Raden Budi Setiadi; Hernadewita Hernadewita (Green Publisher Indonesia, 2026)
The nickel smelting industry in Indonesia generates substantial volumes of slag waste, which pose significant environmental risks if not managed effectively. This study aims to develop a utilization model for nickel slag employing a dynamic systems approach over the 2025–2034 time horizon. The research utilizes secondary data obtained from smelter company reports, relevant literature, and scenario simulations constructed using Powersim. The simulation outcomes reveal a progressive increase in slag generation that is disproportionate to the available processing capacity, resulting in the accumulation of unmanaged nickel slag. Scenario-based optimization demonstrates that enhancing processing capacity by approximately 5%–10% annually can markedly reduce the volume of unmanaged slag. These results underscore the importance of adopting a circular economy framework to support sustainable nickel slag utilization within the smelting industry.